Health related physical fitness of school children (6 to 10 years) from Azores Islands, Portugal - Francisco Pina de Morais; André Seabra; Rui Garganta da Silva; Vitor Pires Lopes; José António Ribeiro Maia (Universidade Federal de Santa Catarina, 2004)
ABSTRACT The purposes of this research were: (1) to investigate health related physical fitness (HPF) of school children (6 to 10 years) from Azores islands, Portugal, and to (2) analyse sex differences in each age. The sample comprised 3742 children of both sexes, residents in Azores islands, Portugal. Twenty-five percent of the children in each gender and age in each island were evaluated with FITNESSGRAM: 1-mile run/walk, curl-ups, push-ups, trunk lift and body mass index (BMI) (kg/m-2). Data were analysed as follow: χ2 to test the differences in ratio of success/failure in each age group; factorial ANOVA gender*age) to test the differences between age groups and gender; discriminant function to test the presence of multivariate profiles of HPF in age natural groups. The ratios of success in both boys and girls were low. In girls there was a substantial decrease of ratio of success between 6 and 10 years of age. Among 10-year-old girls the global ratio of success was only 18%. In boys, the ratios of success had also a tendency to decrease along age. Among 10-years-old boys the global ratio of success was 39%. Boys had better performance in all tests than girls of all ages. Discriminant function analyses indicated that there were a low percentage of children classified in their natural age groups. Although there were children with HPF level advanced for their natural age groups, there were a considerable number of children with HPF level lower than the expected for their own age. RESUMO Pretendeu-se (1) conhecer os níveis da aptidão física associada à saúde (ApFS) da população escolar de 6 a 10 anos de idade do arquipélago dos Açores, Portugal e (2) analisar as diferenças entre os sexos ao longo da idade. A amostra foi constituída por 3742 crianças, de ambos os sexos, residentes no arquipélago dos Açores. A avaliação da ApFS foi efectuada de acordo com a bateria de testes FITNESSGRAM: corrida/marcha da milha, curl-ups, push-ups, trunk lift e índice de massa corporal (kg/m-2). Foram utilizados os procedimentos usuais para descrever as variáveis, bem como: χ2 para testar as diferenças entre os sexos nas taxas de sucesso em cada grupo etário; ANOVA factorial (sexo*idade) para testar as diferenças entre grupos etários e entre os géneros sexuais; função discriminante para verificar a presença de perfis multivariados da ApFS em cada grupo etário. As taxas de sucesso quer dos meninos e das meninas são baixas. Em ambos os sexos ocorre um decréscimo acentuado do sucesso ao longo de idade. Nas meninas, aos 10 anos, a taxa de sucesso global em todas as provas é somente de 18%, enquanto que nos meninos é de 39%. Em todas as provas os meninos apresentam desempenhos médios superiores aos das meninas, qualquer que seja a idade. Embora haja crianças com perfil de ApFS correspondente a faixas etárias mais elevadas, existe um número muito elevado de crianças de ambos os sexos com perfil de ApFS abaixo do que seria de esperar para a sua idade.